Targeting a novel bone degradation pathway in primary bone cancer by inactivation of the collagen receptor uPARAP/Endo180. Issue 1 (30th November 2015) - Engelholm, Lars H; Melander, Maria C; Hald, Andreas; Persson, Morten; Madsen, Daniel H; Jürgensen, Henrik J; Johansson, Kristina; Nielsen, Christoffer; Nørregaard, Kirstine S; Ingvarsen, Signe Z; Kjær, Andreas; Trovik, Clement S; et al.
Abstract: In osteosarcoma, a primary mesenchymal bone cancer occurring predominantly in younger patients, invasive tumour growth leads to extensive bone destruction. This process is insufficiently understood, cannot be efficiently counteracted and calls for novel means of treatment. The endocytic collagen receptor, uPARAP/Endo180, is expressed on various mesenchymal cell types and is involved in bone matrix turnover during normal bone growth. Human osteosarcoma specimens showed strong expression of this receptor on tumour cells, along with the collagenolytic metalloprotease, MT1–MMP. In advanced tumours with ongoing bone degeneration, sarcoma cells positive for these proteins formed a contiguous layer aligned with the degradation zones. Remarkably, osteoclasts were scarce or absent from these regions and quantitative analysis revealed that this scarcity marked a strong contrast between osteosarcoma and bone metastases of carcinoma origin. This opened the possibility that sarcoma cells might directly mediate bone degeneration. To examine this question, we utilized a syngeneic, osteolytic bone tumour model with transplanted NCTC‐2472 sarcoma cells in mice. When analysed in vitro, these cells were capable of degrading the protein component of surface‐labelled bone slices in a process dependent on MMP activity and uPARAP/Endo180. Systemic treatment of the sarcoma‐inoculated mice with a mouse monoclonal antibody that blocks murine uPARAP/Endo180 led to a strong reduction of bone destruction. Our findings identify sarcoma cell‐resident uPARAP/Endo180 as a central player in the bone degeneration of advanced tumours, possibly following an osteoclast‐mediated attack on bone in the early tumour stage. This points to uPARAP/Endo180 as a promising therapeutic target in osteosarcoma, with particular prospects for improved neoadjuvant therapy. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.